2012
DOI: 10.5021/ad.2012.24.1.32
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Genotype and Antimicrobial Susceptibility of High- and Low-Level Mupirocin Resistant Methicillin-ResistantStaphylococcus aureus

Abstract: BackgroundMupirocin has been used for the treatment of skin infections and eradication of nasal carriage of methicillin-resistant Staphylococcus aureus (MRSA). The increased use of this antibiotic has been accompanied by outbreaks of MRSA that are resistant to mupirocin.ObjectiveThis study aims to determine the prevalence, genotype and antimicrobial susceptibility of mupirocin-resistant MRSA from 4 Korean hospitals.MethodsA total 193 MRSA clinical isolates were collected from four university hospitals. Antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
2
23
0
6
Order By: Relevance
“…Mupirocin resistance may be helpful in the spread of multidrug resistance through co-selection with other resistance genes. Previous reports found that mupirocin-resistant S. aureus isolates were multi-resistant to other antimicrobial agents, such as ciprofloxacin, clindamycin, and tetracycline (21,22). Similarly, in present study, mupirocinresistant S. epidermidis were also multi-drug resistant to other antimicrobial agents.…”
Section: Discussionsupporting
confidence: 62%
“…Mupirocin resistance may be helpful in the spread of multidrug resistance through co-selection with other resistance genes. Previous reports found that mupirocin-resistant S. aureus isolates were multi-resistant to other antimicrobial agents, such as ciprofloxacin, clindamycin, and tetracycline (21,22). Similarly, in present study, mupirocinresistant S. epidermidis were also multi-drug resistant to other antimicrobial agents.…”
Section: Discussionsupporting
confidence: 62%
“…Cadilla et al found an association between strains of mupirocin-resistant MRSA and resistance to three or more non-beta-lactam antimicrobial classes (21). Mupirocin-resistant MRSA strains isolated from several hospitals in Korea were also resistant to ciprofloxacin, clindamycin, and tetracycline (22).…”
mentioning
confidence: 99%
“…This confirms the effectiveness of O. glandulosum oil treatment. In addition, there is an urgent need to look for other substances to replace mupirocin because of the spread of S. aureus resistant strains to this molecule (Park et al, 2012).…”
Section: Discussionmentioning
confidence: 99%